Macroinvertebrates Diversity in Sundak Beach, Gunung Kidul, Yogyakarta - Yunita Fera Rahmawati (Biota, 2021)
Macroinvertebrate diversity is one of the biologicals and ecological indicators that allow it to become a reference in determining water quality. This study aimed to inventory and study the diversity of macroinvertebrate species using the 1 x 1 m2 transect method along the Sundak Beach, Gunung Kidul, Yogyakarta. The research was conducted on Sunday, October 13th, 2019, with a quadratic transect method of 10 stations from the lowest low tide to the middle of the sea. The data obtained in this study was the result of macroinvertebrates species inventory in each sampling point and the number of individuals of each species. The data was then analyzed using the Shannon-Weiner diversity index (H'). The results showed 45 macroinvertebrate species with 2590 numbers of individuals were found on the Sundak Beach. The most common species were Gastropods with 16 species, while the most individual species were Ophiuroidea (730 species). The diversity index of 1.28351 indicates that the diversity of macroinvertebrates in Sundak Beach is categorized as medium diversity.